The Use of the Merdeka Mengajar Platform in Implementing the Merdeka Belajar Curriculum at SMAN 2 Sungai Rumbai - Sari, Dara Puspita; Syoviana, Elvi; Andre, Lesis; Syam , Fadhli (The Future of Education Journal, 2025)
This study is motivated by the need for digital transformation in the implementation of the Merdeka Curriculum, particularly through the use of the Merdeka Mengajar Platform (PMM) at SMAN 2 Sungai Rumbai. This platform is expected to support flexible, contextual, and student-centered learning. However, its application still encounters several technical and non-technical obstacles. The purpose of this research is to examine the use of PMM based on indicators such as user activity, availability of training materials, teachers' participation in self-paced training, availability of interactive features, and assessment tools; and to identify the supporting and inhibiting factors in its implementation. This research used a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The participants were the school principal, vice principal for curriculum, and teachers of SMAN 2 Sungai Rumbai. The data were analyzed through data reduction, presentation, and conclusion drawing, with source triangulation to ensure data validity. The results showed that: activity in PMM was inconsistent; only some teachers used the platform regularly, The training materials available were comprehensive, but not fully utilized due to time constraints, Teachers' participation in self-training varied, depending on their motivation and administrative workload, Interactive features such as forums and communities were underutilized due to a lack of familiarity, The assessment feature had not been fully implemented due to a lack of technical guidance. Supporting factors included internet access, support from the school principal, and availability of Belajar.id accounts. Inhibiting factors involved low digital literacy, high teacher workload, limited ongoing training, and resistance to new technology. It is concluded that the PMM platform has strong potential to support the Merdeka Curriculum, but its effective use requires intensive training, infrastructure improvements, and better time management strategies at the school level.